Analysis of the application of inventory accounting and fixed asset accounting to regional work units in Soppeng district - Ria Irawati (Institute of Accounting Research and Novation (IARN), 2023)
This study aims to determine the suitability of the application of inventory accounting and fixed asset accounting with the applicable standards, which are applied to the Soppeng District Civil Service and Education and Training Agency. Inventory accounting in question includes inventory recognition, inventory measurement, and inventory expenses as well as inventory disclosure. While the accounting for fixed assets in question includes the recognition, measurement, expenses after acquisition, depreciation, retirement and disposal as well as disclosure of fixed assets. The applicable standard referred to in this research is Accrual-Based Government Accounting Standard Statement Number 05 concerning inventory accounting and Number 07 concerning fixed asset accounting, which is contained in Government Regulation Number 71 of 2010. The data collection technique used is documentation. Documentation is the collection of data that supports this research, such as proof of transactions, journals, to the financial reports of the Regional Civil Service and Education and Training Agency for the 2015 fiscal year. Data analysis was carried out using a comparative descriptive analysis technique. The results of this study indicate that inventory accounting and fixed asset accounting for the Soppeng Regency Regional Personnel and Education and Training Agency are mostly in accordance with applicable standards. As for the inappropriate accounting treatment, including: recognition of inventories using the expense approach that has not used the accrual basis, errors in recognizing fixed assets in the form of construction in progress, and not disclosing the useful lives of fixed assets and depreciation rates for fixed assets.